Agronomic biofortification of cereals with zinc: a review - Cakmak, Ismail; Kutman, Umit Baris (Wiley, 2018)
Zinc (Zn) still represents an important health problem in developing countries, caused mainly by inadequate dietary intake. A large consumption of cereal‐based foods with small concentrations and low bioavailability of Zn is the major reason behind this problem. Modern cultivars of cereals have inherently very small concentrations of Zn and cannot meet the human need for Zn. Today, up to 50% of wheat‐cultivated soil globally is considered poor in bioavailable Zn. Agricultural strategies that are used to improve the nutritional value of crop plants are known as biofortification strategies. They include genetic biofortification, which is based on classical plant breeding and genetic engineering for larger nutrient concentrations, and greater agronomic biofortification, which is based on optimized fertilizer applications. This review focuses on agronomic biofortification with Zn, which has proved to be very effective for wheat and also other cereal crops including rice. Molecular and genetic research into Zn uptake, transport and grain deposition in cereals are critically important for identifying ‘bottlenecks’ in the biofortification of food crops with Zn. Transgenic plants with large Zn concentrations in seeds are often tested under controlled laboratory or glasshouse conditions with sufficient available Zn in the growth medium for the entire growth period. However, they might not always show the same performance under ‘real‐world’ conditions with limited chemical availability of Zn and various stress factors such as drought. What purpose can an upgraded transport and storage system serve if the amount of goods to be transported and stored is limited anyway? Given the fact that the Zn concentrations required to achieve a measurable impact on human health are well above those required to avoid any loss of yield from Zn deficiency, providing crop plants with sufficient Zn through the soil and foliar fertilizer strategy under field conditions is critically important for biofortification efforts.Zinc malnutrition is a major global health issue associated with cereal‐based diets. Agronomic biofortification with Zn aims to provide edible parts of crop plants with sufficient Zn. Biofortification with Zn fertilizers, particularly foliar applications, works well for wheat and other cereals. Agronomic biofortification with Zn provides a practical and cost‐effective option to tackle the global Zn malnutrition problem.Zinc malnutrition is a major global health issue associated with cereal‐based diets.Agronomic biofortification with Zn aims to provide edible parts of crop plants with sufficient Zn.Biofortification with Zn fertilizers, particularly foliar applications, works well for wheat and other cereals.Agronomic biofortification with Zn provides a practical and cost‐effective option to tackle the global Zn malnutrition problem.